Vantera Mediated Quantification of Urine Citrate and Creatinine: A New Technology to Assess Risk of Nephrolithiasis - Steven P. Matyus; Justyna Wolak-Dinsmore; Erwin Garcia; Randolph M. Young; Margery A. Connelly (Diagnostics, 2022)
Urine citrate is often used to identify patients at risk of recurrent nephrolithiasis or kidney stones. A high-throughput assay was developed to measure urine citrate and creatinine on the Vantera® Clinical Analyzer, a nuclear magnetic resonance (NMR) instrument designed for the clinical laboratory. Assay performance was evaluated and comparisons between the NMR and chemistry results were conducted. Linearity was demonstrated over a wide range of concentrations for citrate (6 and 2040 mg/L) and creatinine (2.8 and 1308 mg/dL). Intra-and inter-assay precision (%CV) ranged from 0.9 to 3.7% for citrate and 0.4 to 2.1% for creatinine. The correlation coefficients for the comparison between NMR and chemistry results were 0.98 (Y = 1.00X + 5.0) for citrate and 0.96 (Y = 0.968X + 0.97) for creatinine. The reference intervals for both analytes were confirmed. Ten endogenous and exogenous substances were tested and none were found to interfere with the assay results. In conclusion, the newly developed high-throughput NMR assay exhibited robust performance and generated results comparable to the currently utilized chemistry tests, thereby providing an alternative means to simultaneously quantify urine citrate and creatinine for clinical and research use. Furthermore, the NMR assay does not exhibit the same interference limitations as the chemistry tests and it enables multiplexing with other urine metabolite assays which saves time and costs.